Parametric method for unsteady two-dimensional MHD boundary-layer on a body for which temperature varies with time (Archives of Mechanics - Test, 2011)
This paper concerns unsteady two-dimensional laminar temperature magnetohydrodynamic (MHD) boundary-layer of incompressible fluid. The present magnetic field is homogenous and perpendicular to the body surface along which the boundary-layer is developing. Body temperature varies with time. Outer electric filed is neglected and magnetic Reynolds number is significantly lower than one, i.e. the considered problem is in induction-less approximation. In order to solve the described problem, multiparametric (generalized similarity) method is used and so-called universal equations are obtained. The obtained universal equations are solved numerically in appropriate approximation and a part of the obtained results is given in the form of figures and the corresponding conclusions.